JAKOŚĆ W MEDYCYNIEProgramme to improve hand hygiene in a paediatric cardiac surgery department - Jaworski, Radosław; Haponiuk, Ireneusz; Chojnicki, Maciej; Irga, Ninela; Wiśniewska, Bogumiła; Treder, Ewa; Ziółkowska, Iwona; Steffens, Mariusz; Zieliński, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Introduction: Hand hygiene plays a great role in programmes for control of hospital infections. It is extremely important especially in cardiosurgical treatment of congenital heart defects in children. The aim : The aim was to assess the effectiveness of a programme to improve hand hygiene in a cardiosurgical department for children based on alcohol-based hand disinfectant consumption measurement. Material and methods : Hand-hygiene retrospective analysis was performed in the Department of Paediatric Cardiac Surgery, Pomeranian Centre of Traumatology in Gdansk, according to hand disinfectant consumption measurement. Afterwards the author’s designed hand hygiene improving programme was applied. Another hand disinfectant consumption measurement was made after 6 months of observation. Results : Before introducing the hand hygiene improvement programme there were 204 patients admitted with 582 patient-days of hospitalization, 88 surgical interventions and a mean 2.85-day hospitalization period in 6 months of observation. After introduction of the hand hygiene compliance improvement programme there were 175 patients admitted with 665 patient-days of hospitalization, 118 surgical interventions and a mean 3.8-day hospitalization period in another 6 months of observation. The mean alcohol-based hand disinfectant usage rate per patient-day in the first and the second observation period was 11.9 and 33 respectively (p < 0.001). There were no differences in incidence of healthcare-associated infections between the observed periods. Conclusions : Our interventions led to significantly better hand disinfectant usage and indirectly hand hygiene improvement. No differences in incidence of healthcare-associated infections were observed because of the short observation period; longer term observations and continuation of the programme are required.